2005
DOI: 10.1520/gtj12196
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Shear Wave Velocity Using Bender Elements

Abstract: The use of bender element to measure shear wave velocity is popular due to its simplicity. However, there are still some uncertainties in the interpretation of the bender element test. In this paper, the use of bender elements in the determination of shear wave velocities of dry, unsaturated, and saturated soil specimens is examined with respect to the characteristics of the bender elements, waveform, magnitude, and frequency of the applied voltage to the transmitter bender element and method of travel time de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…For the start-to-start method, the noise level is very significant. Leong et al [40] verified the criteria for the improvement of the interpretation of the BE test, among which there is the signal-to-noise ratio (SNR) criterion. According to their research, the SNR should be of at least 4 dB for the receiver signal.…”
Section: Test Setup and Proceduresmentioning
confidence: 99%
“…For the start-to-start method, the noise level is very significant. Leong et al [40] verified the criteria for the improvement of the interpretation of the BE test, among which there is the signal-to-noise ratio (SNR) criterion. According to their research, the SNR should be of at least 4 dB for the receiver signal.…”
Section: Test Setup and Proceduresmentioning
confidence: 99%
“…Cruse and Rizzo (1968) and Sanchez-Salinero et al (1986) analytically predicted the presence of near field components in shear waves traveling through a medium. Experimental observations further confirmed the presence of near field effects (Brignoli et al 1996;Leong et al 2005). Arroyo et al (2003) described the near field component in the arriving shear waves as a "distorted and transposed replica of the input signal".…”
Section: Background and Problem Statementmentioning
confidence: 60%
“…Depending on the cement content, water content and curing time, a range of input frequencies are utilized to consider the varying stiffness values of all mix ratios in this study. Consequently, it is demonstrated that the study successfully establishes the reliability of the proposed function in correcting V s values obtained at lower L tt /λ ratios to more accurate V s values that correspond to standardized L tt /λ ratios of 2, 3.33 and 4 (Leong et al 2005;Sanchez-Salinero et al 1986).…”
Section: R a F T Introductionmentioning
confidence: 65%
See 2 more Smart Citations